Modulation of the Endocannabinoid System as a Potential Anticancer Strategy - Ramer, Robert; Schwarz, Rico; Hinz, Burkhard (Frontiers in Pharmacology, 2019)
Currently, the involvement of the endocannabinoid system in cancer development and possible options for a cancer-regressive effect of cannabinoids are controversially discussed. In recent decades, a number of preclinical studies have shown that cannabinoids have an anticarcinogenic potential. Therefore, especially against the background of several legal simplifications with regard to the clinical application of cannabinoid-based drugs, an extended basic knowledge about the complex network of the individual components of the endocannabinoid system is required. The canonical endocannabinoid system consists of the endocannabinoids N-arachidonoylethanolamine (anandamide) and 2-arachidonoylglycerol as well as the Gi/o coupled transmembrane cannabinoid receptors CB1 and CB2. As a result of extensive studies on the broader effect of these factors, other fatty acid derivatives, transmembrane and intracellular receptors, enzymes and lipid transporters have been identified that contribute to the effect of endocannabinoids when defined in the broad sense as "extended endocannabinoid system". Among these additional components of cannabinoid activity, the endocannabinoid-degrading enzymes fatty acid amide hydrolase and monoacylglycerol lipase, lipid transport proteins of the fatty acid-binding protein family, additional cannabinoid-activated G protein coupled receptors such as GPR55, members of the transient receptor family, and peroxisomal proliferator-activated receptors were identified as targets for possible strategies to combat cancer progression. Other endocannabinoid-related fatty acids such as 2-arachidonoylglyceryl ether, O-arachidonoylethanolamine, N-arachidonoyldopamine and oleic acid amide showed an effect via cannabinoid receptors, while other compounds such as endocannabinoid-like substances exert a permissive effect on cannabinoid receptors and act via alternative intracellular target structures. This overview gives an overview of the modulation of the extended endocannabinoid system using the example of anticancer cannabinoid effects, which have been described in detail in preclinical studies.